1994
DOI: 10.1159/000247113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluid Volume Changes during Hemodialysis on the Biophysical Parameters of the Skin

Abstract: Water plays an important role in maintaining skin suppleness and elasticity. We used hemodialysis as a model to investigate the effects on biophysical properties of the skin induced by removal of fluids and water from the body. The following parameters have been investigated before and immediately after a hemodialysis session: body weight, skin elasticity and distensibility, skin hydration, transepidermal water loss (TEWL) and skin thickness. A significant decrease was recorded after treatment in body weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Brazzelli et al [7] noticed that acute fluid removal after a single HD session reduced skin thickness and elasticity at volar forearm. In this study, we found that skin water content both at forearm and leg was increased after a single HD session ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Brazzelli et al [7] noticed that acute fluid removal after a single HD session reduced skin thickness and elasticity at volar forearm. In this study, we found that skin water content both at forearm and leg was increased after a single HD session ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…T HE OVERALL mechanical properties of human skin depend mainly on the nature and organisation of the dermal collagen and elastic fiber network, water, proteins and macromolecules embedded in the extracellular matrices (1), with some contribution by the epidermis and the stratum corneum (2)(3). The investigation of the mechanical properties of healthy and diseased skin allows both quantitative and qualitative assessment of certain dermal alterations (4)(5)(6)(7)(8), enabling evaluation of treatment efficacy (9)(10)(11)(12)(13). The efficacy of cosmetic products in terms of emolliency (2,14) and hydration (15), and the effects of skin ageing can also be observed by the study of the mechanical properties of skin (1,9,(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…It is well‐known that increased fluid intake increases the water content in the dermis because the water accumulates in this layer . An increased water content in the dermis may also increase the water content in the epidermis . A higher epidermal water content may change the water concentration gradient between the SG and the outer SC cells.…”
Section: Discussionmentioning
confidence: 99%
“…32 An increased water content in the dermis may also increase the water content in the epidermis. 33 A higher epidermal water content may change the water concentration gradient between the SG and the outer SC cells. On the other hand such a simplified view may be wrong because the water content of the SC is largely determined by the natural moisturizing factors, the structure of the corneocytes and the SC intercellular lipids.…”
Section: Discussionmentioning
confidence: 99%